2003
DOI: 10.1063/1.1534627
|View full text |Cite
|
Sign up to set email alerts
|

Transparent thin film transistors using ZnO as an active channel layer and their electrical properties

Abstract: Bottom-gate-type thin film transistors using ZnO as an active channel layer (ZnO–TFT) have been constructed. The ZnO layers were deposited using pulsed laser deposition at 450 °C at an oxygen pressure of 3 m Torr, and the material that was formed had a background carrier concentration of less than 5×1016 cm−3. A double layer gate insulator consisting of SiO2 and SiNx was effective in suppressing leakage current and enabling the ZnO–TFT to operate successfully. The Ion/Ioff ratio of ZnO–TFTs fabricated on Si wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
324
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 539 publications
(331 citation statements)
references
References 22 publications
5
324
0
2
Order By: Relevance
“…[2][3][4][5][6][7][8][9] 최근에는 저온 성장, 높은 전계 효 과 이동도(field effect mobility, 0.2-40 cm 2 /Ns), 우수한 on-off 비율(10 3 -10 6 ), 높은 가시광 파장 투명도 등이 요구 되는 투명 박막 트랜지스터(transparent thin-film transistor, TTFT)에 ZnO를 이용하는 연구가 진행되고 있다. [10][11][12] ZnO 박막을 형성하기 위한 방법으로 스퍼터링(sputtering) 과 펄스 레이저 증착법(pulsed laser deposition, PLD)과 같은 물리 기상 증착법(physical vapor deposition, PVD) 이 사용되어 왔다. 12,13) 하지만, 최근에는 정확한 두께 조 절과 우수한 표면 균일성 등의 장점을 갖는 원자층 증착 법(atomic layer deposition ALD)을 이용하여 ZnO가 증착 되고 있다.…”
Section: 서 론unclassified
“…[2][3][4][5][6][7][8][9] 최근에는 저온 성장, 높은 전계 효 과 이동도(field effect mobility, 0.2-40 cm 2 /Ns), 우수한 on-off 비율(10 3 -10 6 ), 높은 가시광 파장 투명도 등이 요구 되는 투명 박막 트랜지스터(transparent thin-film transistor, TTFT)에 ZnO를 이용하는 연구가 진행되고 있다. [10][11][12] ZnO 박막을 형성하기 위한 방법으로 스퍼터링(sputtering) 과 펄스 레이저 증착법(pulsed laser deposition, PLD)과 같은 물리 기상 증착법(physical vapor deposition, PVD) 이 사용되어 왔다. 12,13) 하지만, 최근에는 정확한 두께 조 절과 우수한 표면 균일성 등의 장점을 갖는 원자층 증착 법(atomic layer deposition ALD)을 이용하여 ZnO가 증착 되고 있다.…”
Section: 서 론unclassified
“…Masuda et al [17] reported a ZnO channel layer with bottom-gate structure, exhibiting low carrier concentration (<5 × 10 16 cm −3 ). The ZnO layer was deposited onto a silicon substrate by pulsed-laser deposition (PLD) at a substrate temperature of 450°C, under oxygen atmosphere.…”
Section: Operation Of the Tfts And Important Device Parametersmentioning
confidence: 99%
“…A variety of metals such as Al [9], In [10], and Au/Ti [11] have been used as source/drain electrodes for AOS TTFTs. Among them, Al is the most desirable electrode because of its extremely low resistivity, good adhesion, and weldability.…”
Section: Introductionmentioning
confidence: 99%